BENTUK, STRATEGI PENGGUNAAN, DAN KESANTUNAN TINDAK TUTUR MENOLAK DALAM INTERAKSI ANTARMAHASISWA PRODI SASTRA PRANCIS FBS UNNES (Lingua, 2010)
The problems that were examined: (1) how the realization of speech act of refuser in French by the researchsubjects are used? (2) what strategies are used by research subjects in refuser to their partners? and (3) howthe politeness levels are used in the Speech Act of refuser by Semester VI Students?Data obtained by â€œfishingâ€ techniques, â€œfishingâ€ the respondents using a questionnaire. The data wereanalyzed using equivalent analytical methods subtypes with a pragmatic â€œtool partners of the respondents